COMPETITIVENESS, DISPOSITIVENESS AND OFFICIAL CLARIFICATION OF ALL CIRCUMSTANCES OF A CASE IN ADMINISTRATIVE LEGAL PROCEEDINGS - Mahda, S. O. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2017)
the article is devoted to the problem of the application by administrative courts of the principles of administrative legal proceedings, in particular the principle of competition, discretion and official clarification of all circumstances of the case. The prospects of reforming the national legislation for the effective protection of the rights, freedoms and interests of the person by the court during the consideration and resolution of administrative cases are determined.